2001
DOI: 10.1016/s0301-0082(00)00030-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive motor control in crayfish

Abstract: This article reviews the principles that rule the organization of motor commands that have been described over the past five decades in crayfish. The adaptation of motor behaviors requires the integration of sensory cues into the motor command. The respective roles of central neural networks and sensory feedback are presented in the order of increasing complexity. The simplest circuits described are those involved in the control of a single joint during posture (negative feedback-resistance reflex) and movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 196 publications
(269 reference statements)
0
65
0
Order By: Relevance
“…For example, animals that travel fast through water exhibit a tightly coordinated wavelike motor program that is produced centrally in the absence of sensory feedback [see Hill et al (Hill et al, 2003) and references therein]. In contrast, in legged locomotion, where properties of the substrate with which the legs interact can drastically change, local information about current leg states plays an essential role in coordinating the limbs (Cattaert and Le Ray, 2001;Pearson, 2004;Ritzmann and Büschges, 2007;Borgmann et al, 2007;Borgmann et al, 2009). An important context-specific role for sensory feedback was also suggested by Johnston and Levine (Johnston and Levine, 2002), following their detailed analysis of differences between patterned motor activities evoked from isolated larvae or adult central nervous systems in Manduca, and activity patterns observed in the intact animals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, animals that travel fast through water exhibit a tightly coordinated wavelike motor program that is produced centrally in the absence of sensory feedback [see Hill et al (Hill et al, 2003) and references therein]. In contrast, in legged locomotion, where properties of the substrate with which the legs interact can drastically change, local information about current leg states plays an essential role in coordinating the limbs (Cattaert and Le Ray, 2001;Pearson, 2004;Ritzmann and Büschges, 2007;Borgmann et al, 2007;Borgmann et al, 2009). An important context-specific role for sensory feedback was also suggested by Johnston and Levine (Johnston and Levine, 2002), following their detailed analysis of differences between patterned motor activities evoked from isolated larvae or adult central nervous systems in Manduca, and activity patterns observed in the intact animals.…”
Section: Introductionmentioning
confidence: 99%
“…In legged locomotor systems, sensory input signaling leg displacement and force or strain to central neuronal networks is pivotal for generating functional walking motor outputs (Orlovsky et al, 1999;Pearson, 2000;Cattaert and LeRay, 2001;Büschges, 2005). Load information from the legs plays a particularly important role because stable walking requires effective load distribution across all legs during stance (Duysens et al, 2000;Zill et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We first examined recruitment among a subset of motor neurons that reach firing threshold in response to sensory input from a proprioceptive organ (Cattaert and Le Ray, 2001;El Manira et al, 1991;Le Ray et al, 1997a;Le Ray et al, 1997b). We found that neurons with small extracellular spikes are more susceptible to fire than motor neurons with medium or large spikes, indicating that there is an orderly recruitment of motor neurons.…”
Section: Introductionmentioning
confidence: 99%